Prenatal diagnosis of genetic aberrations in fetuses with pulmonary stenosis in southern China: a retrospective analysis - Meiying Cai; Nan Guo; Meimei Fu; Yuqing Chen; Bin Liang; Yanting Que; Qingqiang Ji; Hailong Huang; Liangpu Xu; Na Lin (BMC, 2023)
Abstract Background The genetic etiology of congenital pulmonary stenosis (PS) in fetuses remains inadequately studied. We used karyotype analysis and chromosomal microarray analysis (CMA) to investigate the genetic aberrations associated with PS in human fetuses. Methods A retrospective analysis was performed on 84 fetuses with congenital PS in southern China. Fetal amniotic fluid and umbilical cord blood samples were obtained for chromosomal karyotype analysis and CMA. Results The rate of pathogenic copy number variation (CNV) was 15.5% (13/84) after karyotyping and CMA. An abnormal karyotype was detected in five cases (6.0%, 5/84) via karyotyping, whereas pathogenic CNVs were detected in 13 cases (15.5%, 13/84) via CMA. In addition to the five abnormal karyotypes detected using karyotype analysis, eight additional chromosomal microduplications and microdeletions were detected using CMA, comprising three cases of 22q11.21 microdeletion; two cases of 16p11.2 microdeletion; one case of simultaneous 18q23 microdeletion and 22q13.33 microduplication; one case of 15q24.1q24.2 microdeletion; and one case of 1q21.1q21.2 microduplication. The rate of pathogenic CNV occurrence was 11.5% in fetuses with isolated PS and 17.2% in fetuses with PS combined with other ultrasound abnormalities. This difference between the two experimental groups was statistically significant. Among 84 fetuses with PS, 39 pregnancies were terminated, and five were lost to follow-up. Conclusions CMA was not only conducive to detect PS-related pathogenic genomic abnormalities but also to accurately evaluate fetal prognosis in genetic counseling. The early detection of PS and genomic abnormalities will exerta positive impact on fetal intervention and the related prognosis of PS in perinatal infants.